1994
DOI: 10.1093/clinchem/40.6.862
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reference values for urinary organic acids in a healthy Turkish pediatric population

Abstract: Organic acid concentrations were quantified by gas chromatography and the individual acids identified by mass spectrometry in urine specimens from a healthy Turkish pediatric population of ages 2 days to 16 years, subdivided into five age groups. We quantified 69 organic acids (32 major and 37 minor components) and report here the median values and percentiles for each compound, adjusted for creatinine content, for the five groups. Concentrations of most of the organic acids tend to decrease with age but displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
36
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 0 publications
12
36
1
Order By: Relevance
“…This particular metabolic situation seems to be reflected in the reduced urinary excretion of certain organic acids (including butyric and isobutyric acid) compared to older individuals where glycogen stores are fully restored [31]. Furthermore, indoleacetic acid measured in our neonatal cohort were also found to be 10-fold lower than what has been reported in the literature for neonates [32]. Both HPHPA and indoleacetic acid are known gut microbial metabolites, with HPHPA excretion being associated with gut microbial degradation of dietary phenylalanine or polyphenols [33] and indoleacetic acid being a microbially derived breakdown product of tryptophan [33].…”
Section: Comparison Of Experimental Values With Reported Reference Vacontrasting
confidence: 48%
“…This particular metabolic situation seems to be reflected in the reduced urinary excretion of certain organic acids (including butyric and isobutyric acid) compared to older individuals where glycogen stores are fully restored [31]. Furthermore, indoleacetic acid measured in our neonatal cohort were also found to be 10-fold lower than what has been reported in the literature for neonates [32]. Both HPHPA and indoleacetic acid are known gut microbial metabolites, with HPHPA excretion being associated with gut microbial degradation of dietary phenylalanine or polyphenols [33] and indoleacetic acid being a microbially derived breakdown product of tryptophan [33].…”
Section: Comparison Of Experimental Values With Reported Reference Vacontrasting
confidence: 48%
“…Lack of statistical significance can be attributed to high variability in the citrate concentrations in each group. It has been reported that citrate can be highly variable in human urine as a result of various individual metabolic processes 31. Other endogenous compounds like steroids can also be expected to be different in male and female urine samples as sex differences in steroid metabolism have been clearly demonstrated in clinical studies 32.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in urine organic acids profiles also have been reported in populations of healthy infants, with the highest median urinary MMA (95th percentile) of 5.2 (49) mmol/mol creatinine and 29.9 (78.9) mmol/mol creatinine seen at 1 and 6 months of age. 41,42 Concentrations tend to decrease with age because of the steady increase in creatinine excretion as infants develop, especially up to the age of 6 months. 41 The effect of creatinine excretion on urinary MMA concentration may be similar in dogs, but this factor has not been assessed.…”
Section: Discussionmentioning
confidence: 99%